1971
DOI: 10.1111/j.1348-0421.1971.tb00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Phage Receptor Material in Lactobacillus casei Cell Wall

Abstract: A trichloroacetic acid (TCA)-soluble fraction, extracted using cold TCA, was derived from the cell wall of Lactobacillus casei strain S-1. It not only inhibited the adsorption of phage J-1 but also de-orbed these phages, in their active form, which had previously been adsorbed onto the cell walls. L-Rhamnose, one of the components of this TCAsoluble fraction, had an identical activity to this TCA-soluble fraction, on phage adsorption. This suggested that L-rhamnose is a part of phage receptor material in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
0
0

Year Published

1976
1976
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 17 publications
(14 reference statements)
1
0
0
Order By: Relevance
“…Similar results were reported for Gram-positive bacteria like B. subtilis [19], S. aureus [24], and A-and C-streptococci [25]. In contrast, soluble extracts obtained after extraction of Lactobacillus casei S-1 cell walls with 5% TCA were active in inhibiting phage adsorption [26]. In our investigation, inhibition of phage adsorption after preincubating cell walls of both strains with the lectins Concanavalin A and wheat germ agglutinin was not observed.…”
Section: Resultssupporting
confidence: 89%
“…Similar results were reported for Gram-positive bacteria like B. subtilis [19], S. aureus [24], and A-and C-streptococci [25]. In contrast, soluble extracts obtained after extraction of Lactobacillus casei S-1 cell walls with 5% TCA were active in inhibiting phage adsorption [26]. In our investigation, inhibition of phage adsorption after preincubating cell walls of both strains with the lectins Concanavalin A and wheat germ agglutinin was not observed.…”
Section: Resultssupporting
confidence: 89%
“…Although the prototypic phage-host studies of phages of lactobacilli identified LTA and TA receptors, it was known that other interactions were also occurring. Most significant among these was the study undertaken to elucidate the interaction between L. casei phages PL-1 and J-1, with their respective hosts revealing that L-rhamnose was implicated as a necessary component of the phage receptor because it blocked phage J-1 adsorption to its host, L. casei J-1, following incubation with the monosaccharide (Yokokura 1971). Subsequent assays were undertaken using phage J-1, its host L. casei J-1, and a phage J-1-resistant derivative L. casei S-1.…”
Section: Lactobacillus Sppmentioning
confidence: 99%
“…2014a; M.-E. Dieterle et al 2017a;Yokokura 1971). Moreover, the involvement of Rhamnose, present in CWPs of Gram-positive bacteria, in host recognition has been extended to other phages (Guérin, Kulakauskas, and Chapot-Chartier 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In J-1 phage, Dit protein has two carbohydrate-binding modules (CBM1 and CBM2), but only CBM2 seems to be involved in bacterial cell wall polysaccharides (CWPs) recognition (M. E. Dieterle et al 2014b;Vinogradov et al 2016a; M.-E. Dieterle et al 2017a). The CWP of L. casei BL23 is rich in a-Rhamnose (Vinogradov et al 2016b) and previous results showed that J-1 phage adsorption to L. casei cells was inhibited in the presence of this monosaccharide, leading to the idea that the interaction must be mediated by rhamnose (Yokokura 1971;M. E. Dieterle et al 2014b; M.-E. Dieterle et al 2017b).…”
Section: Introductionmentioning
confidence: 93%